Competency Mapping Practices and Organisational Development: Evidence it Companies in Bengaluru - Madhumati Kadkol; F.X Virgin Fraga (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
Competency mapping has become an integral human resource management practice for aligning employee capabilities with organisational objectives, particularly in knowledge-intensive industries. The present study assesses competency mapping practices and examines their perceived contribution to organisational development among employees working in selected Information Technology companies in Bengaluru. A quantitative research approach was adopted using a descriptive cross-sectional survey design. Primary data were collected from 400 employees through a structured questionnaire and descriptive statistics, including mean, standard deviation and ranking analysis, were used for data analysis with IBM SPSS Statistics (Version 29). The findings show that competency mapping practices are widely adopted across the selected organisations, with Competency Identification, Skill Development and Organisational Productivity emerging as the most prominent dimensions. Employees also perceived competency mapping as making a significant contribution to organisational development through stronger strategic alignment, effective workforce utilisation, greater employee commitment and improved organisational adaptability. The study establishes the importance of competency mapping in strengthening organisational capability and supporting sustainable organisational development within the Information Technology sector.